21st-century Japanese management : New systems, lasting values - Abegglen, James C. (Palgrave Macmillan, 2006)
The book analyzes the evolution of Japanese management in the 21st century, emphasizing its enduring values and adaptive systems. Abegglen examines corporate structures, employment practices, and cultural foundations that shape Japanese business, highlighting how tradition and innovation combine to sustain competitiveness in a globalized economy